Creative Strategies of Producers in Attracting Viewer Interest in The World of Moslem Program on Muslim Tv MNC Channels - Ramadanika, Helen Novia; Trianita, Yanti (Universitas Pendidikan Nasional, 2025)
The advancement of communication and information technology has a significant impact on the world of television broadcasting in Indonesia, one of which is through the phenomenon of media convergence. Following this development, the producers of Muslim TV have developed strategies to improve the quality and quantity of programs. This research aims to examine the Creative Strategies of Producers in Attracting Viewer Interest in the program World of Moslem on Muslim TV MNC Channels. Using a post-positivist paradigm and qualitative descriptive method, this study involves the Producers of Muslim TV as subjects and the program World of Moslem as the object. Peter Pringle's Program Strategic Management Theory serves as the basis for analysis. Data were collected through observation, documentation, the internet, and interviews with the production team. The results show four stages of strategy: (1) Planning, where producers play an essential role in determining the program's vision, mission, and identity (2) Production and program procurement, with a focus on joint collaboration Vlogger and internal coordination (3) Execution, including scheduling and promotion on social media (4) Supervision and evaluation, with the producer reviewing content before airing and evaluating based on rating and share data. In conclusion, the producer places greater emphasis on the planning stage, particularly in the selection of vloggers and material development. Production is carried out to the fullest, but at the post-production stage, the producer delegates more tasks to the production team, although supervision is still carried out through content reviews